EFFECTS OF PHYSICAL ACTIVITY IN MUSCLE ULTRASOUND EVALUATION OF AN OLDER ADULT POPULATION - A PILOT STUDY - Rute Santos; Helena Ferraz (Brazilian Society of Geriatrics and Gerontology, 2021)
INTRODUCTION: Insufficient physical activity levels in aging populations have become an increasing challenge. The phenotype of sarcopenia has many causes in addition to aging. The presence of low muscle performance is necessary for diagnosis, in addition to low muscle mass. The ultrasound is an imaging modality with several advantages, making it potentially useful in assessing muscle changes. OBJECTIVE: This pilot study aimed to evaluate muscle morphology changes in older adults after a physical activity program using ultrasound parameters. METHODS: Older adults aged over 60 years were divided into two non-randomized groups in an unblinded trial: an intervention group (n = 18), who took part in a physical activity program for 8 weeks; and a control group, whose members were encouraged to maintain their usual daily routines (n = 16). All the participants were submitted to bilateral quadriceps muscle ultrasound evaluations; the thickness and echo-intensity muscles were analyzed. Only six participants of each group were available for a second evaluation session. The t-test for independent samples was used to evaluate differences between the groups. A t-test for paired samples was performed for the IntG at baseline and post-intervention. RESULTS: Muscle thickness showed a negative correlation with age, while echo-intensity showed a positive correlation. Echo-intensity showed a negative correlation with muscle thickness. There were differences between the groups for both measurement. CONCLUSIONS: A change in muscle morphology was noticeable when a physical activity program was applied in this pilot study. New studies are necessary to confirm these preliminary findings. Ultrasound could be a low-cost objective method for muscle evaluation in physical activity programs assessment in older adults.